A novel AlGaN/GaN hybrid-anode current regulating diode (CRD) with step-graded Schottky-Ohmic cathode. (November 2018) - Gao, Wei; Dong, Changxu; Zhou, Qi; Hu, Kai; Shi, Yuanyuan; Wei, Dong; Zhu, Liyang; Zhang, Anbang; Shi, Yu; Cheng, Qian; Chen, Wanjun; Zhang, Bo
Abstract: In this work, a novel AlGaN/GaN lateral current regulating diode was proposed and studied. The diode features a MIS-Gated hybrid anode enabling flexibly tailor the forward turn-on voltage and reverse blocking characteristics of the diode. Meanwhile, instead of utilizing the conventional Ohmic cathode, the cathode of the proposed CRD consists a step-graded Schottky extension connecting with the Ohmic contact, which endows the CRD with excellent current regulation capability. The drive current capability, knee voltage and current steadiness can be precisely modulated by tailoring the gradient and length of the Schottky extension at the cathode. The proposed CRD with such a new functionality is of great potential to expand the applications of AlGaN/GaN electronic devices. Highlights: The diode features a MIS-Gated hybrid anode and a step-graded Schottky extension in the cathode. The step-graded Schottky extension possesses an excellent current regulation capability. The forward turn-on voltage and reverse blocking characteristics of the diode can be flexibly tailored by the MIS-Gated hybrid anode. The knee voltage and current steadiness can be modulated by tailoring the gradient and length of the Schottky extension.